Маркетингові дослідження як інструмент визначення стратегічних напрямків розвитку підприємства - Шквиря, Наталя Олександрівна; Шквыря, Наталья Александровна; Shkvyria, Natalia; Сокіл, Яна Сергіївна; Сокол, Яна Сергеевна; Sokil, Yana (My University, 2020)
UK: В даній статті представлені результати дослідження споживчих переваг і основних вимог цільового ринку для розроблення стратегічних напрямків молокопереробних підприємств щодо вдосконалення маркетингової діяльності. Здійснено оцінку стану попиту на молочну продукцію, виявлено цінову чутливість споживачів, ставлення респондентів до якості молочних продуктів, проаналізовано впізнаваність торгових марок регіональних виробників молочних продуктів. Детерміновано фактори впливу на прийняття рішення про купівлю споживачем молочної продукції та визначено роль комунікаційної політики, зокрема Інтернет-реклами у досягненні такої мети. EN: Successful commercial enterprise activity in the market conditions involves considering the individual needs of different groups and categories of customers. To this end, each company is interested in market research and analysis of potential consumers. This is especially true for the dairy industry. Research results. The results of consumer preferences and basic requirements of the target market investigation for the development of strategic directions of dairy enterprises to improve marketing activities are revealed in the article. The demand conditions for dairy products have been evaluated, the price sensitivity of consumers has been revealed, the respondents' attitude to the quality of dairy products has been analyzed, and the brand awareness of regional dairy producers has been assessed. The factors influencing the decision to buy dairy products are determined and the role of communication policy, in particular Internet advertising, in achieving this goal is determined. Internet advertising is a fast growing segment of the media and communications market, including the popularity of the platform with thematic information resources and targeted advertising on social networks. Email marketing is the least attractive to Internet users, and most ignore it. Conclusions. The article summarizes that the assortment strategy of dairy companies with a processing plant is to update and expand the custom-tailored range, and the activation of communication activities is carried out using of marketing communications tools in the digital space. The necessity of increasing organic products in production (replacement of artificial nutritional supplements with natural ones) is underlined in the article. The strategic growth priorities are compliance with production standard and improving the quality of dairy products.
Marketing research as a mechanism for determining the strategic areas of enterprise development
Keywords: маркетингові дослідження; молокопереробне підприємство; анкетування; стратегічні напрямки розвитку; marketing research; dairy processing company; survey; strategic directions of development